Aproveitamento da torta residual de sementes de pinhão Manso (jatropha curcas l.) para a obtenção da curcina: uma rna-nglicosidase com potencial biotecnológico - Veras, José Iran Pereira (2015)
The use of the residual Jatropha curcas seeds pie been limited due to the presence of toxic, allergenic and anti-nutritional factors. In part, this toxicity is attribute to a RIP type 1 called curcin. The curcin is a RNA N-glucosidase with great biotechnological potential, because it presents several biological activities, including anticancer action. The objective of this study was to evaluate the viability of utilization of the residual pie from J. curcas seeds to obtain the of curcin bioactive form. Initially, the seeds pie (with 15 days old) was delipidated with hexane for 12 h and transformed into a fine and homogeneous powder. This powder was submitted to proteins extraction (1: 10 w / v) with PBS buffer pH 7.2, for 4 h, at 25 °C. The total extract was centrifuged at 12000 xg for 20 min at 4 °C. The supernatant was collected submitted to 60% saturation with ammonium sulfate for 6 h at 5 °C. The solubilized protein fraction was dialyzed and applied to a Sephadex G-100. Five major protein peaks were obtained of the chromatographic process. The fraction corresponding to peak 4 was pooled and analyzed by electrophoresis (SDS-PAGE). A single protein band of apparent molecular weight of 28 KDa was observed, similar to curcin from seeds. This fraction corresponding to curcin seeds pie (CSP) was also able of depurinate (in vitro) the ribosomal RNA from Pichia pastoris and to inhibit (in vitro) protein synthesis of luciferase. The results of acute toxicity assay in mice showed that CSP presented a LD50 of 60 mg/kg. Circular dichroism assays have shown that the CTS has a predominance of -sheets and its melting temperature is around 65 °C The polyclonal antibody anti-CTS was able to specifically recognize the curcin seeds. In conclusion, even after 15 days of storage, the residual pie from J. curcas seeds could be used for obtaining of the bioactive curcin, stable and functional.